What is #f(x) = int sinx-cos^2x dx# if #f(pi/6)=2 #?

Answer 1

#f(x)=-[cosx+x/2+1/4*sin2x]+(48+15sqrt(3)+2pi)/24#

#f(x)=int(sinx-cos^2x)dx# #f(x)=int(sinx-1/2(1+cos2x))dx=[-cosx-1/2(x+(sin2x)/2)]+c# #f(x)=[-cosx-x/2-1/4*sin2x]+c#, #to (1)# #f(pi/6)=[-cos(pi/6)-pi/12-1/4*sin(pi/3)]+c=2=>[-sqrt(3)/2-pi/12-1/4sqrt(3)/2]+c=2=>-[sqrt(3)/2+pi/12+1/4sqrt(3)/2]+c=2##=>-(12sqrt(3)+2pi+3sqrt(3))/24+c=2=>c=2+(15sqrt(3)+2pi)/24# #.c=(48+15sqrt(3)+2pi)/24#, #to (2)# From (1) and (2) #f(x)=-[cosx+x/2+1/4*sin2x]+(48+15sqrt(3)+2pi)/24#
Sign up to view the whole answer

By signing up, you agree to our Terms of Service and Privacy Policy

Sign up with email
Answer 2

To find ( f(x) = \int (\sin x - \cos^2 x) , dx ) given that ( f(\frac{\pi}{6}) = 2 ), integrate the expression ( \sin x - \cos^2 x ) with respect to ( x ) and then use the given value to determine the constant of integration.

First, integrate ( \sin x - \cos^2 x ) with respect to ( x ):

[ \int (\sin x - \cos^2 x) , dx = -\cos x - \frac{1}{3}\cos^3 x + C ]

Where ( C ) is the constant of integration.

Given that ( f(\frac{\pi}{6}) = 2 ), substitute ( x = \frac{\pi}{6} ) and solve for ( C ):

[ 2 = -\cos\frac{\pi}{6} - \frac{1}{3}\cos^3\frac{\pi}{6} + C ]

[ 2 = -\frac{\sqrt{3}}{2} - \frac{1}{3}\left(\frac{\sqrt{3}}{2}\right)^3 + C ]

[ 2 = -\frac{\sqrt{3}}{2} - \frac{1}{3}\left(\frac{3\sqrt{3}}{8}\right) + C ]

[ 2 = -\frac{\sqrt{3}}{2} - \frac{\sqrt{3}}{8} + C ]

[ 2 = -\frac{4\sqrt{3} + \sqrt{3}}{8} + C ]

[ 2 = -\frac{5\sqrt{3}}{8} + C ]

[ C = 2 + \frac{5\sqrt{3}}{8} ]

Thus, the function ( f(x) = \int (\sin x - \cos^2 x) , dx ) with ( f(\frac{\pi}{6}) = 2 ) is:

[ f(x) = -\cos x - \frac{1}{3}\cos^3 x + 2 + \frac{5\sqrt{3}}{8} ]

Sign up to view the whole answer

By signing up, you agree to our Terms of Service and Privacy Policy

Sign up with email
Answer 3

To find the function ( f(x) = \int \sin(x) - \cos^2(x) , dx ) when ( f(\frac{\pi}{6}) = 2 ), we need to evaluate the integral and then find the function.

Given that ( f(\frac{\pi}{6}) = 2 ), we can use this information to find the constant of integration.

First, we evaluate the integral:

[ \int \sin(x) - \cos^2(x) , dx ]

[ = -\cos(x) - \frac{1}{3} \sin^3(x) + C ]

Now, we plug in ( x = \frac{\pi}{6} ) to find the constant of integration ( C ):

[ -\cos(\frac{\pi}{6}) - \frac{1}{3} \sin^3(\frac{\pi}{6}) + C = 2 ]

[ -\frac{\sqrt{3}}{2} - \frac{1}{3} \left(\frac{1}{2}\right)^3 + C = 2 ]

[ -\frac{\sqrt{3}}{2} - \frac{1}{24} + C = 2 ]

[ C = 2 + \frac{\sqrt{3}}{2} + \frac{1}{24} ]

Thus, the function ( f(x) = \int \sin(x) - \cos^2(x) , dx ) is:

[ f(x) = -\cos(x) - \frac{1}{3} \sin^3(x) + 2 + \frac{\sqrt{3}}{2} + \frac{1}{24} ]

Sign up to view the whole answer

By signing up, you agree to our Terms of Service and Privacy Policy

Sign up with email
Answer from HIX Tutor

When evaluating a one-sided limit, you need to be careful when a quantity is approaching zero since its sign is different depending on which way it is approaching zero from. Let us look at some examples.

When evaluating a one-sided limit, you need to be careful when a quantity is approaching zero since its sign is different depending on which way it is approaching zero from. Let us look at some examples.

When evaluating a one-sided limit, you need to be careful when a quantity is approaching zero since its sign is different depending on which way it is approaching zero from. Let us look at some examples.

When evaluating a one-sided limit, you need to be careful when a quantity is approaching zero since its sign is different depending on which way it is approaching zero from. Let us look at some examples.

Not the question you need?

Drag image here or click to upload

Or press Ctrl + V to paste
Answer Background
HIX Tutor
Solve ANY homework problem with a smart AI
  • 98% accuracy study help
  • Covers math, physics, chemistry, biology, and more
  • Step-by-step, in-depth guides
  • Readily available 24/7